Nutrient and Nitrate Composition of Greenhouse-Grown Leafy Greens: A Trial Comparison Between Conventional and Organic Fertility Treatments - Swanson, Erin O.; Carlson, Justin L.; Perkus, Liz A.; Grossman, Julie; Rogers, Mary A.; Erwin, John E.; Slavin, Joanne L.; Rosen, Carl J. (Frontiers in Sustainable Food Systems, 2022)
Arugula (Eruca sativa), mizuna (Brassica rapa var. nipponsinca), red giant mustard (Brassica juncea) and spinach (Spinaciaoleracea “Tyee”) are fresh produce crops high in nutritive value and provide shortfall and high interest nutrients addressed in the 2015 U.S. Dietary Guidelines. The primary objective of this project was to evaluate fertility treatments unique to these crops that optimize their nutritional capacity. Measurements discussed include: vitamin C, dietary fiber, calcium, iron, potassium, sodium and nitrate. Plants were grown at the University of Minnesota St. Paul Campus (St. Paul, MN) in a greenhouse from November to April under an 18 h photoperiod and a 24/13 °C day/night temperature. Plants were grown using five different fertility treatments, including four organic treatments and one conventional control. The plant treatment combinations were replicated three times and the entire experiment was duplicated. Fertility treatments had a high impact on vitamin C (with over a 3-fold difference in treatments in the first experiment), nitrate (over 10-fold difference among fertility treatments in some species) and potassium concentrations (over 5-fold difference among fertility treatments in some species) in analyzed plant tissue. No consistent differences were found for fiber, calcium, iron and sodium concentrations in tissue analyzed. This is the first study to analyze the impact that different organic treatments can have on multiple deficient nutrients and compounds addressed by the U.S. Dietary Guidelines for high-impact, highly-consumed produce crops.